Digitalization as a problem or solution? Charting the path for research on sustainable information systems - Daniel J. Veit; Jason B. Thatcher (Journal of Business Economics, 2023)
Digitalization has permeated all aspects of human lives, economies, and societies. This transformation has been driven by the rapid growth in computing power, storage capabilities, and data transmission infrastructures. These changes have enabled innovations, such as cloud computing, artificial intelligence, smartphones, digitalized homes, (semi) autonomous vehicles, quantum computing, and more. Digitalization has further resulted in faster, more effective service delivery by many organizations. The phenomenon of digitalization relies on an increasingly finite supply of resources, such as crude oil, silicon, and energy. Over the past 150~years, humans have consumed as many natural resources as they have consumed in the past 20,000~years. In part, this increasing clip of consumption has been driven by digitalization, as novel, technology-based solutions, such as blockchain, supplant older, slower low-tech solutions, such as books and ledgers, to process data and create value. Digitalization's demand for resources may be leading us to an environmental abyss. Consider cryptocurrencies such as Bitcoin, whose electricity consumption is approximately equal to the energy needs of small nations such as Malaysia or Sweden. Such consumption evokes the question, is, "is more digitalization really better, or given the harm to the planet, is this one context where less is more?". In this paper, we develop a research agenda for understanding the full cost of digitalization and its impact on sustainability. We do so in three parts; first, we offer a crisp definition of sustainability; second, we offer a concise review of the digitalization and sustainability literature; and third, we offer suggestions for research that advances our understanding of how digitalization impacts sustainability.
Keywords: M00; M15; Q01; Q55; 650; Digitalization; Sustainability; Sustainable development; Environmental sustainability; Social sustainability; Economic sustainability; Green IT; Green IS